Citra dan peran perempuan dalam film Indonesia di era pandemi 2020-2022 - Hidayat, Kammala Nur; Rengganis, Ririe; Tjahjono, Tengsoe (Universitas Lampung, 2023)
This research is a literary criticism that sees women as readers or observers of Indonesian films in the pandemic era in 2020-2022. This study aims to find out how women are constructed and how the role of women in Indonesian films in the pandemic era. This research is classified as qualitative descriptive research with literature method as a data collection technique. And the content analysis method as a data analysis technique with steps including creating data tables, classifying data based on problem formulations and analyzing data based on research interpretation. The results of this study show that women obtain oppression constructed in forms of injustice that include marginalization, subordination, stereotypes, physical and non-physical violence and workload caused by the culture that has developed in society. Meanwhile, the role of women is played with an image adapted to the culture that has existed before, namely women who are only aware of the oppression carried out by the ruling class and hesitate to fight back. Keywords: Image, role, woman, pandemic era